OPTIMALISASI ELEMEN VISUAL UNTUK TRANSFORMASI PSIKOLOGIS PADA PENYUTRADARAAN FILM BATAPATIH - Willy Furqan; Adri Yandi; Nitasri Murawaty Girsang (Institut Seni Indonesia Padang Panjang, 2023)
Batapatih is a drama genre film that tells the story of a child born in Minang named Ryan who has long lived in Jakarta with his father who is busy working and his mother who has long died, this makes Ryan feel no love from his parents. This situation makes Ryan trapped in bad company. His father, Ridwan, who is suffering from a chronic disease, makes him worried about Ryan's future, so his father invites Ryan to return to Minangkabau.The fictional film Batapatih was worked on by taking visual elements into the concept used in making the film because the background of this Batapatih scenario is to tell the story of teenagers who do not get love from their parents because their fathers are busy working and their mothers have died, when Ryan was brought to the village. by his father Ryan began to understand what the meaning of a life. So to show the change in Ryan's character, this concept is used so that the information to be conveyed can be visualized properly, information is not only conveyed through dialogue but also by visualization of Ryan's attitude, the movements he makes and also his response to the environment. The concept of visual elements can visualize dramatic as well as emotional situations.